The Effectiveness of Tawandakulo (Kleinhovia Hospita L.) On SGOT, SGPT Enzyme Levels, and Hepatocyte Regeneration in Paracetamol-Induced Rats - Saranani, Muhaimin; Nurfantri, Nurfantri (YCAB Publisher, 2024)
Background:Paracetamol is metabolized by cytochrome P450 enzymes into a highly toxic reactive metabolite, N-acetyl-p-benzoquinonimine (NAPQI), which can cause liver damage. Antioxidants play a crucial role in mitigating liver toxicity. Kleinhovia hospitaL. (also known as Tawandakulo) is a potent plant antioxidant due to its content of secondary metabolites, such as phenolics, flavonoids, saponins, and terpenoids. Objective:This study aimed to investigate the levels of SGOT and SGPT enzymes, as well as liver histopathology, as indicators of liver health. Methods:An experimental research design with a randomized post-test control group was used. The study involved 25 rats, randomly divided into five groups. Paracetamol was administered at a toxic dose of 2.5 g/kg body weight, dissolved in distilled water, and given orally through NGT no. 5. Results:The study found a decrease in SGOT levels in the treatment group and a significant reduction in SGPT enzyme levels between pre-intervention (P2) and post-intervention (P3). There was a significant change in enzyme levels in treatment group 2 (p = 0.00) and treatment group 3 (p = 0.03). However, no significant difference was observed in treatment group 4 (p = 0.09). Liver cells in treatment groups P1, P2, and P3 showed signs of regeneration, whereas cells in the control group did not regenerate. Group P4 exhibited slower liver cell regeneration than the other treatment groups. Conclusion:This study concludes that a decoction of Kleinhovia hospitaL. can stimulate liver cell growth and reduce SGOT and SGPT enzyme levels. Keywords: Kleinhovia hospitaL; SGOT; SGPT; Liver cell regeneration; Indonesia.